Karakteristik Analisis Wacana Kritis Dalam Wacana Berita “ Stebi Gelar Seminar Ekonomi Kreatif” - Melvin Arfiandita; Dessy Saputry; Amy Sabila (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2024)
Characteristics in Critical Discourse Analysis (AWK) include action, context, history, power, and ideology. When viewed from the news coverage of the Mina tragedy, it can be analyzed according to these five characteristics. The purpose of this study is to describe the characteristics of critical discourse analysis in the news discourse